1996
DOI: 10.1152/jappl.1996.81.2.636
|View full text |Cite
|
Sign up to set email alerts
|

Altitude acclimatization and blood volume: effects of exogenous erythrocyte volume expansion

Abstract: We studied sea-level residents during 13 days of altitude acclimatization to determine 1) altitude acclimatization effects on erythrocyte volume and plasma volume, 2) if exogenous erythrocyte volume expansion alters subsequent erythrocyte volume and plasma volume adaptations, 3) if an increased blood oxygen content alters erythropoietin responses during altitude acclimatization, and 4) mechanisms responsible for plasma loss at altitude. Sixteen healthy men had a series of hematologic measurements made at sea l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
2
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 0 publications
5
57
2
1
Order By: Relevance
“…Sawka and others (1996) found that erythrocyte volume did not change after 13-days of continuous high altitude exposure and that plasma volume decreased by around 10%. 82 Other studies have shown similar results. [83][84][85][86] An adequate plasma volume is quite necessary for cardiac function during maximal exercise and to ensure that blood can be properly transported throughout the circulatory system.…”
Section: Effects Of Acute Altitude Residence On Plasma Volumementioning
confidence: 52%
See 1 more Smart Citation
“…Sawka and others (1996) found that erythrocyte volume did not change after 13-days of continuous high altitude exposure and that plasma volume decreased by around 10%. 82 Other studies have shown similar results. [83][84][85][86] An adequate plasma volume is quite necessary for cardiac function during maximal exercise and to ensure that blood can be properly transported throughout the circulatory system.…”
Section: Effects Of Acute Altitude Residence On Plasma Volumementioning
confidence: 52%
“…In the Sawka (1996) study, fluid intake was controlled to prevent dehydration and the weight loss observed was not nearly enough to account for the volume loss seen in the plasma. 82 This study showed for the first time that decreases in plasma oncotic pressures and fluid volume were strongly correlated. He suggests that initially this is due to increased capillary permeability, possibly followed later by an increase in protein degradation.…”
Section: Effects Of Acute Altitude Residence On Plasma Volumementioning
confidence: 71%
“…The physiological mechanisms are the following: 1) increase in the pulmonary ventilation 39 ; 2) reduction in the HR previously increased in the acute response 22,39 ; 3) decrease in the plasmatic volume 39,40 ; 4) reduction of the accumulation of lactate in the blood during submaximal exercise in relation to the more elevated levels of acute response 39 ; 5) improvement of the cardiorespiratory capacity for exercise, also related to the initial exposure to the hypobaric hypoxia 23,41 ; 6) increase in the secretion of renal erythropoietin, in the hemoglobin mass and in the hematocrit 34,36,37,42 .…”
Section: Acclimatizationmentioning
confidence: 99%
“…Physiological variables that contribute to the increase in submaximal endurance capacity with altitude acclimatization include an increase in exercise minute ventilation (VE) (21,77) and decrease in plasma volume (PV) (39,96,101,113). These changes cause respective increases in arterial oxygen saturation (Sa0 2 ) and hemoglobin concentration ([Hb]).…”
Section: Introductionmentioning
confidence: 99%
“…These changes cause respective increases in arterial oxygen saturation (Sa0 2 ) and hemoglobin concentration ([Hb]). The increase in [Hb] occurs primarily due to a decrease in PV since red blood cell mass and erythropoietin concentration ([EPO]) are not increased after a 2-3 wk altitude acclimatization period (61,96). Since arterial oxygen content (Ca0 2 ) is determined by both Sa0 2 and [Hb], Ca0 2 is reduced upon initial ascent to altitude, due to the lower partial pressure of arterial oxygen (Pa0 2 ), and increased with altitude acclimatization (35).…”
Section: Introductionmentioning
confidence: 99%